Wspólny system powrotów Unii Europejskiej – ku zwiększeniu skuteczności powrotów obywateli państw trzecich. Analiza porównawcza postępowania w zakresie powrotów na podstawie dyrektywy 2008/115 i projektu rozporządzenia ustanawiającego wspólny system powrotów (COM (2025) 101) - Strąk, Katarzyna (PRAWO i WIĘŹ, 2025)
The article provides a comparative analysis of the return procedure under Directive 2008/115 and under recently tabled regulation establishing a common European return system The aim of the proposed reform is to make EU return policy more effective, still based on the 2008 Directive, and to adapt it to the challenges arising from the development of migration and asylum law within the European Union. The conclusion is that the Commission’s proposal will, at least in theory, have a positive impact on the effectiveness of returns of third-country nationals staying illegally in the territory of Member States. This will be due to the appropriate choice of legal instrument, namely an EU regulation, which provides for uniform application of its provisions in all Member States, but also due to the fact that it leaves Member States a certain degree of flexibility.